Addition - Jordan, Toni (London : Sceptre, 2008)
In Melbourne, Australia, a neurotic, 35 year old woman who loves to count meets an Irish transplant named Seamus Joseph O'Reilly and with some gentle encouragement decides to give love a chance. Can she find a happy medium between her obsession and living life to its fullest?
Keywords: Tesla, Nikola, -- 1856-1943 -- Fiction; Women -- Australia -- Melbourne (Vic.) -- Fiction; Obsessive-compulsive disorder -- Fiction; Counting -- Fiction; Melbourne (Vic.) -- Fiction